2019
DOI: 10.1037/xge0000610
|View full text |Cite
|
Sign up to set email alerts
|

Is the public understanding of memory prone to widespread “myths”?

Abstract: It is frequently asserted that the understanding of memory among the general public and among legal and psychological professionals is deficient, the most prominent examples being that many people appear to liken memory to a video camera, overestimate the association between accuracy and confidence, and believe in repression. The existing evidence is limited to single questionnaire items, however, and to date there has been little investigation of context effects or of the public's underlying assumptions about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(63 citation statements)
references
References 65 publications
5
54
3
Order By: Relevance
“…We agree that work using the Think/No Think or directed forgetting paradigm can be construed as evidence that deliberate blocking of memories can sometimes make a memory harder to retrieve. However, we disagree with Brewin et al (2019) that their survey statement on this issue is related to paradigms such as Think/No Think or directed forgetting paradigm. The statement that Brewin et al used ("Traumatic experiences can be deliberately blocked for many years and then recovered") focused on the assertion that traumatic experiences can be consciously suppressed for many years.…”
Section: Deliberate Repressioncontrasting
confidence: 84%
See 1 more Smart Citation
“…We agree that work using the Think/No Think or directed forgetting paradigm can be construed as evidence that deliberate blocking of memories can sometimes make a memory harder to retrieve. However, we disagree with Brewin et al (2019) that their survey statement on this issue is related to paradigms such as Think/No Think or directed forgetting paradigm. The statement that Brewin et al used ("Traumatic experiences can be deliberately blocked for many years and then recovered") focused on the assertion that traumatic experiences can be consciously suppressed for many years.…”
Section: Deliberate Repressioncontrasting
confidence: 84%
“…Participants were compensated with $0.25. In Study 3 of Brewin et al (2019), 80 university students were tested.…”
Section: Participantsmentioning
confidence: 99%
“…This average estimate was significantly higher than the rate of false memory we observed in the current study, as well as that observed in most false memory studies (Loftus, 2005). Given the ongoing debate concerning public perceptions of memory reliability and whether nonpsychologists perceive memory to work 'like a video camera' (Brewin et al, 2019;Otgaar et al, 2020;Simons & Chabris, 2011), this high estimate is noteworthy.…”
Section: Discussioncontrasting
confidence: 53%
“…Furthermore, we assessed whether previous participation in our false memory study may have been educational; specifically, we evaluated whether participants estimated false memories to be more or less common if they had previously taken part in a false memory study and been debriefed. There is debate as to how widespread memory myths are amongst the general public (Brewin et al, 2019;Otgaar et al, 2020;Simons & Chabris, 2011) and it is unclear if participation in a false memory study impacts these opinions.…”
mentioning
confidence: 99%
“…Lay understanding of many aspects of eyewitness memory has improved over time (Desmarais & Read, 2011), with an increasing proportion of respondents reporting beliefs in line with eyewitness experts regarding factors such as pre‐lineup instructions, cross‐race identifications, and post‐event information (see also Simons & Chabris, 2011). Recent evidence further indicates that lay beliefs in “memory myths” may be artifacts of survey construction, and actual lay beliefs about memory may be more in line with science than previously thought (Brewin, Li, Ntarantana, Unsworth, & McNeilis, 2019). This suggests that jurors have (at least some of) the requisite knowledge of eyewitness factors to accurately evaluate eyewitness evidence; the issue is devising a way to encourage jurors to apply that knowledge to the case at hand.…”
Section: Eyewitness Evidence and Juror Evaluationsmentioning
confidence: 94%